Periodicals of the Ukrainian SSR in the 1950-1980s as a Tool for Influence on Fashion and Everyday Life - Корнієнко, Ольга (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2019)
The article deals with the mechanisms of periodicals’ impact on fashion and everyday life in the Ukrainian SSR. The activity of censorship boards to control the content of periodicals is revealed. It focuses on the mainstreaming of the fashion theme in the second half of the 20th century and analyzes its coverage on the example of the most popular and diverse magazines of the USSR (“Radianska zhinka”, “Perets”, “Krasa i moda”). The conclusion was drawn that Ukrainian magazines actively used their tools to form “necessary” ideas and place “correct” emphasis about fashion.